Mitochondrial phospholipid synthesis and incorporation - Hatch, Grant (Henry Stewart Talks, 2007)
Mitochondrial phospholipids and their biosynthetic pathways: how to study mitochondrial phospholipid synthesis using radiotracer studies, Examples of regulation of mitochondrial phospholipid biosynthesis, Regulation of de novo cardiolipin biosynthesis by phospholipid scramblase-3, Regulation of de novo phosphatidylethanolamine biosynthesis during cardiac cell differentiation, Mitochondrial phospholipid remodeling, Regulation of cardiolipin resynthesis in rat liver regeneration
Reviewed at 2018/06/01